ANALISIS BIAYA PRODUKSI DAN NILAI TEGAKAN PENGUSAHAAN HUTAN ALAM : Kasus suatu perusahaan di propinsi sumatera selatan - Rachman Effendi; Yetti Setyowati; Tien Wahyuni (Jurnal Penelitian Hasil Hutan, 1996)
The main source of revenue for forestry  development up to now still depends on natural forest  which is the main source of wood for  the industries. In the utilization of natural forest  the assessment  of  stumpage  value  is  important  to  determine  the profit  margin  that  goes  to goverment as well as to the concession holder.The  objective  of  this  study  is  to  get  clear  picture  on  the  cost  components  of forest concession and to know the stumpage value of forest  land.  To determine the stumpage value a production  cost analysis was done based on a year operation of concession holder.The  results  showed  that  the  cost  components  of  log production  consists  of planning, building main road and skidding road, road maintenance and log houling with total production cost Rp.  58.480,- per  m3 for felled  area of  1000 ha with production  of meranti and mixed species each 22.003,47   m3  and 7. 720, 78 m3,  respectively. Based on profit ratio 35% which went to concession holder there is still surplus which the goverment presently does not collect as forest   owner. Based  on  this  result goverment  revenue in  the forms  of  forest  product  fee, reforestation fund and concession fee can be increased up to 200% from present level.Key Word  : Natural  Forest,  Stumpage  Value,   Forest Concession, Production Cost, Forest Product Fee,  Reforestation Fund, Concession Fee.